Zero Waste Circular Model of MSWM: A Success in Ward 40, Pune, India. Issue 1 (June 2019) - Mastakar, Priti; Mastakar, Vijay; Mukhopadhyay, Kakali; Jaju, Surabhi
The concept of "zero waste" is a dream that has been actualized in only a couple of pockets of the world, mostly developed ones where there is no paucity of funds. It is in the developing nations that innovations have been made towards sustainability due to the non-availability of funds. "Zero waste, " where the entire municipal solid waste is processed with organic processes, is a perfectly sustainable solution to the exponentially rising environmental and civic problem facing today's society. "Zero landfills" is another feature of zero waste. Landfills too involve high costs both private and external costs that get hidden in taxes on already tax-burdened citizens. It then becomes very pertinent to work out sustainable solutions to municipal solid waste management (MSWM). Zero waste with "zero" or minimal waste to landfills creates a sustainable solution to MSWM. We neither keep waste for future generations nor do we incur unnecessary costs of maintaining unsustainable processes. Ward 40 (a ward is an administrative division), Katraj of Pune city from the developing world—the subject of the present research—has established and is running the zero waste model successfully since 2012. Through the present research study, Ward 40 was subject to stringent financial, economic, social and environmental analysis, and it was established that it was indeed a zero waste project.